(untitled) (SCIENCE TIME JOURNAL, 2026)
This article analyzes the semantic and stylistic features of Uzbek proverbs connected with the concept of “mercy” (rahm-shafqat, mehr, muruvvat). The study focuses on how mercy is expressed through moral evaluation, metaphor, antithesis, parallelism, repetition and didactic generalization in Uzbek proverbial discourse. The analysis shows that Uzbek proverbs represent mercy not only as an emotional feeling, but also as a social, ethical and spiritual value that regulates human relationships. Proverbs about mercy usually encourage kindness toward the weak, respect for parents and elders, support for orphans and the poor, and compassion toward all people. The research is based on descriptive, semantic and stylistic methods.